Kanlungan a regional rehabilitation center for the youth. - Evangelista, Kenaz Aron F.; Simoun T. Ong (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The current juvenile justice system in the country is severely neglected, resulting in subpar conditions of prisons and juvenile detention facilities. Children in conflict with the law (CICL) are to be detained in a separate facility from adults as stated in Republic Act 9344 or Juvenile Justice and Welfare Act. However these facilities are usually underfunded or lack enough space to accommodate all cases. As a result, children are not properly reformed and a holistic approach to rehabilitation is not achieved, which may result in future recidivism. In addition, current House Bill 8858 proposes to lower the age of responsibility from 15 to 12 years old, which could potentially bring in more youth into already overcrowded facilities. In recent Philippine National Police and Department of Social Welfare and Development (DSWD) reports, juvenile cases have risen in the National Capital Region. There are now over a thousand cases being reported and investigated, and about three hundred cases that await trial. DSWD has managed to provide regional rehabilitation centers in all regions, except in NCR. And now, with cases starting to go up, the need for a rehabilitation center focused on CICL cases is very much apparent. The proposed project shall try to answer this need. This will be done by examining basic principles and patterns of humane rehabilitation center design and how this could aid the development and reformation of the CICL. This research hopes to bring to light the existing problems in our juvenile system and facilities, and show how architecture could help in bringing restorative justice especially to the youth.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Restorative justice; Rehabilitation centers; Shelter for juvenile delinquents; Children in conflict with the law